Opinion mining on product reviews from document to clause - Ting, Lin (Nanyang Technological University, 2022)
Product reviews contain valuable information about product features and consumers’ purchasing preferences. Overwhelming amounts of such reviews have been generated daily, which demands an automatic opinion mining process on product reviews. On the other hand, sentiment analysis, also known as opinion mining, aims to discover sentiment polarity from opinionated documents. Opinion mining on product reviews involves multiple tasks, which can be categorized into two areas by their analysis granularity: coarse-grained and fine-grained sentiment analysis. However, there are limitations in existing solutions for the tasks. We propose different approaches in this thesis to overcome the challenges in a few tasks of opinion mining on product reviews.